China and The Islamic World : How The New Silk Road is Transforming Global Politics - Bianchi, Robert R. (New York Oxford University Press, 2019)
China is building a New Silk Road that runs through the heartland of the Muslim world, promising it will create integrated economies and stronger ties across Eurasia and Africa. Robert R. Bianchi argues that while China has the financial and technical resources to accomplish its infrastructure goals, it is woefully unprepared to deal with the social and political demands of its partner countries' citizens.
Include Bibliography and Index
Keywords: a